1998
DOI: 10.1128/aac.42.4.801
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of a Mutant of Influenza A Virus Selected with the Neuraminidase Inhibitor BCX-140

Abstract: Influenza neuraminidase (NA) plays an important role in viral replication, and characterization of viruses resistant to NA inhibitors will help elucidate the role of active-site residues. This information will assist in designing better inhibitors targeted to essential active-site residues that cannot generate drug-resistant mutations. In the present study we used the benzoic acid-based inhibitor BCX-140 to select and characterize resistant viruses. BCX-140 binds to the NA active site in an orientation that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Growth inhibition of influenza virus isolates in MDCK cells was performed using a colorimetric method based on the in situ reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) by viable cells, as described elsewhere [20]. The percentage of cell survival was calculated using the for-…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…Growth inhibition of influenza virus isolates in MDCK cells was performed using a colorimetric method based on the in situ reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) by viable cells, as described elsewhere [20]. The percentage of cell survival was calculated using the for-…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…These studies are generally related to altering the activity of HA or NA and observing the relative infectivity or compensatory mutations that occur after passage. Studies involving the inhibition of NA with inhibitors have shown that escape mutants can be generated with substitutions in HA alone (79), and sensitivity to these inhibitors is determined by both HA and NA (3). These substitutions are hypothesized to reduce HA binding, allowing efficient release of virus with reduced NA activity.…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by reducing the affinity of HA to the sialic acid, therefore the progeny virus particles rely less on NA activity when leaving the cell surface (Bantia et al, 1998;Blick et al, 1998;Ginting et al, 2012;McKimm-Breschkin et al, 1996;Molla et al, 2002). Indeed, sequence analyses revealed Fig.…”
Section: Ha Mutationsmentioning
confidence: 95%